KEPUSAN KERJA DITINJAU DARI PERILAKU WORK FAMILY CONFLICT - Dwi Hurriyati (Universitas Katolik Soegijapranata, 2017)
The research purpose is to know that is there is a relation between the work family conflicts with the work satisfaction inPT. Bank Mandiri (Persero) Palembang. The hypothesis that used in this research is that there is a relation between the work family conflicts with works satisfaction on the woman in PT. Bank Mandiri (Persero). The subject used for this research is 150 woman in .Bank Mandiri (Persero). with using the simple regression technique. The analysis result by using the simple regression technique shows that r = 0,378 and p = 0,000 where is p≤0,01 that means there is a significant relation between work family conflict to the work satisfaction on police woman in Bank Mandiri (Persero).The effective contribution given by work family conflict against the work satisfaction on woman in .Bank Mandiri (Persero). is as much as 0,145 or 14,5 %.